2008
DOI: 10.1086/587864
|View full text |Cite
|
Sign up to set email alerts
|

Non–Local Thermodynamic Equilibrium Model of NGC 6543’s Central Star and Its Relation to the Surrounding Planetary Nebula

Abstract: We analyze the chemical composition of the central star of the planetary nebula NGC 6543 based on a detailed NLTE model of its stellar wind. The logarithmic abundances by number are H ¼ 12:00, He ¼ 11:00, C ¼ 9:03, N ¼ 8:36, O ¼ 9:02, Si ¼ 8:19, P ¼ 5:53, S ¼ 7:57, and Fe ¼ 7:24. Compared with the solar abundances, most of the elements have solar composition with respect to hydrogen, except C, which is overabundant by 0.28 dex, and Fe, which is depleted by $0.2 dex. Contrary to most previous work, we find that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Although we assume in our models a single set of abundances for both the nebular and CSPN fast wind material, in reality these could be different, with the CSPN abundances being metal-enriched due to the expulsion of the hydrogenrich envelope (Georgiev et al 2008;Morisset & Georgiev 2009). Thus, the change in the relative importance of the hot, shocked stellar wind gas and the heated nebular material seen in Figure 15 should also manifest itself as an evolution of the abundances responsible for the X-ray spectra of these objects.…”
Section: Discussionmentioning
confidence: 99%
“…Although we assume in our models a single set of abundances for both the nebular and CSPN fast wind material, in reality these could be different, with the CSPN abundances being metal-enriched due to the expulsion of the hydrogenrich envelope (Georgiev et al 2008;Morisset & Georgiev 2009). Thus, the change in the relative importance of the hot, shocked stellar wind gas and the heated nebular material seen in Figure 15 should also manifest itself as an evolution of the abundances responsible for the X-ray spectra of these objects.…”
Section: Discussionmentioning
confidence: 99%
“…For the time being, the existing observations do not seem to be consistent with such a limb brightening. Georgiev et al (2008) found recently that the wind of the central star of NGC 6543 is less depleted in iron compared to the plasma emitting the diffuse X-rays (Georgiev et al 2006). They concluded that the X-ray emitting plasma "is derived from nebular gas rather than the stellar wind".…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum is similar to that of NGC 6572. Georgiev et al (2008) analyzed a high quality spectrum of this star. Although they did not propose any spectral classification, they confirmed that the star is not H poor.…”
Section: Stellar Descriptions and Classifications: Notes On Individuamentioning
confidence: 99%